Physiological and anatomical aspects of the reproduction of mice with reduced Syndecan-1 expression - Christina Gougoula; Alexandra P. Bielfeld; Sarah J. Pour; Jan-S. Krüssel; Martin Götte; W. Peter M. Benten; Dunja M. Baston-Büst (BMC, 2019)
Abstract Background Syndecan-1 is a heparan sulfate proteoglycan acting as a co-receptor for cytokines and growth factors mediating developmental, immunological and angiogenic processes. In human, the uteroplacental localization of Syndecan-1 and its reduced expression in pregnancy-associated pathologies, such as the intrauterine growth restriction, suggests an influence of Syndecan-1 in embryo-maternal interactions. The aim of the present study was to identify the effect of a reduced expression of Syndecan-1 on the reproductive phenotype of mice and their progenies. Methods Reproductive characteristics have been investigated using animals with reduced Syndecan-1 and their wildtype controls after normal mating and after vice versa embryo transfers. Female mice were used to measure the estrus cycle length and the weight gain during pregnancy, as well as for histological examination of ovaries. Male mice were examined for the concentration, motility, viability and morphology of spermatozoa. Organs like heart, lung, liver, kidney, spleen, brain and ovaries or testes and epididymis of 6-month-old animals were isolated and weighed. Statistical analyses were performed using two-tailed students t-test with P < .05 and P < .02, chi square test (P < .05) and Fisher's Exact Test (P < .05). A linear and a non-linear mixed-effects model were generated to analyze the weight gain of pregnant females and of the progenies. Results Focusing on the pregnancy outcome, the Syndecan-1 reduced females gave birth to larger litters. However, regarding the survival of the offspring, a higher percentage of pups with less Syndecan-1 died during the first postnatal days. Even though the ovaries and the testes of Syndecan-1 reduced mice showed no histological differences and the ovaries showed a similar number of primary and secondary follicles and corpora lutea, the spermatozoa of Syndecan-1 reduced males showed more tail and midpiece deficiencies. Concerning the postnatal and juvenile development the pups with reduced Syndecan-1 expression remained lighter and smaller regardless whether carried by mothers with reduced Syndecan-1 or wildtype foster mothers. With respect to anatomical differences kidneys of both genders as well as testes and epididymis of male mice with reduced syndecan-1 expression weighed less compared to controls. Conclusions These data reveal that the effects of Syndecan-1 reduction are rather genotype- than parental-dependent.